Fabrication of plasmonic materials via nanoporous alumina mask - Jung, M.; Kim, S.K.; Lee, S.; Lee, T.; Kim, S.H.; Woo, D.; Kim, J.H. (Technical Digest - 2012 17th Opto-Electronics and Communications Conference, OECC 2012, 2012)
Plasmonic materials have attracted considerable attention because of scientific interest and their potential applications. Using the nanoporous alumina mask as an evaporation mask, Ag nanodot array was directly formed on indium-tin-oxide glass. Its optical properties are studied. ？ 2012 IEEE.